Integrating primary palliative care into hidradenitis suppurativa management - Terri Shih, BS; Monica Zell, MD; Daniel Karlin, MD; Devea R. De, BS; Jan Smogorzewski, MD; Vivian Y. Shi, MD; Jennifer L. Hsiao, MD (Wolters Kluwer, 2022)
Hidradenitis suppurativa (HS) is a chronic, often debilitating skin condition that disproportionately impacts women in the United States and other Western nations. Dermatologists should consider incorporating palliative care principles into HS management to optimize care. Primary palliative care principles include utilizing evidence-based frameworks in serious illness communication, acknowledging and addressing physical and psychosocial suffering, recognizing and validating the burden of disease in partners, families, and caregivers, and engaging in collaborative care coordination. Certain patients may also benefit from outpatient, or sometimes inpatient, palliative care specialist collaboration, such as those with refractory HS and superimposed challenging psychosocial dynamics and symptom burden. Through integration of these palliative care domains into HS care, dermatologists can optimize their ability to provide comprehensive and compassionate care for patients suffering with this disease.